Svidrigajlov and Dunja – Some Notes on Plot Relations in Dostoevskij’s Prestuplenie i nakazanie - Jan Brodal (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2007)
This article explores the relationship between Svidrigajlov and Dunja in Dostoevskij’s novel Prestuplenie and nakazanie (Crime and punishment).